Clinical Findings in Diabetes Mellitus Patients with COVID-19. (11th January 2021) - Guo, Ting; Shen, Qinxue; Ouyang, Xiaoli; Guo, Wei; Li, Jinhua; He, Wenlong; Yu, Bo; Wu, Chenfang; Zhou, Zhiguo; Luo, Hong; Peng, Hong
Abstract : Backgrounds . Diabetes mellitus (DM) is one of the most common comorbidities in patients with coronavirus disease (COVID-19). We aim to summarize the clinical features of DM patients with COVID-19 and find out potential factors associated with severe disease. Methods . In this retrospective, single-center study, the medical records of patients with COVID-19 in Changsha, Hunan, China, from January 21, 2020, to February 19, 2020, were reviewed. Epidemiological information, clinical features, and outcomes were compared between DM patients admitted to the intensive care unit (ICU) or not. Results . A total of 241 patients confirmed with COVID-19 were enrolled, including 19 DM patients. There were more patients in DM group admitted to the ICU than non-DM group (36.8% vs. 15.8%, P = 0.045 ). Compared with non-DM group in the ICU, there were more female patients from DM group in the ICU (85.7% vs. 31.4%, P = 0.024 ). On admission, the mean level of glycated hemoglobin A1c (HbA1c) was higher in the ICU DM patients than that in the non-ICU DM patients (8.5% vs. 7.1%). There were more DM patients with proteinuria in the ICU group than the non-ICU group (57.1% vs. 33.3%). Twelve DM patients (63.2%) changed diabetic therapy during hospitalization, and all DM patients admitted to the ICU used insulin. As of March 14, all 19 DM patients have been discharged, and no death occurred. Conclusions . DM patients with COVID-19 are vulnerable to severe disease, especially for female patients. High levels of HbA1c and proteinuria could be potential risk factors for severe COVID-19 in DM patients. In addition to timely systemic therapy, the control of blood glucose and proper diabetic therapy is essential to improve the prognosis of severe DM patients with COVID-19.